Digital Marketing Development Strategy to Increase the Number of Tourists - Gumilang, Adi Surya Panji; Gandhy, Abel; Prasetyo, Bayu Dwi (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The increase in number of tourists is inseparable from the strategies used by tourist attractions by utilizing social media and Generation Z as a potential segmentation because they are known as digital natives. As happened to Bigstone Riverside located in Bogor, West Java, which once utilized social media by collaborating with influencers and getting an increase in visitors. Unfortunately, because the strategy used was inconsistent, there was a decline in visitors. This research aims to formulate a digital marketing development strategy for Bigstone Riverside. The selection of this research location was carried out purposively because this tourist destination has the potential to be developed and become a source of income for the surrounding community. This research uses qualitative data sourced from primary data and secondary data. The strategy formulation method used SWOT matrix by analyzing internal and external factors. The results of the strategy in this study are alternative strategies such as creating content that highlights advantages, creating promotions so that tourists share their excitement, conducting digital marketing training for administrators, collaborating with influencers and tourist information accounts, utilizing content generated by UGC users, optimizing SEO, and forming a team.